Clinical Characteristics and Outcomes of Hematologic Malignancy Patients With Positive Clostridium difficile Toxin Immunoassay Versus Polymerase Chain Reaction Test Results. (25th April 2018) - Ziegler, Matthew; Landsburg, Daniel; Pegues, David; Alby, Kevin; Gilmar, Cheryl; Bink, Kristen; Gorman, Theresa; Moore, Amy; Bonhomme, Brittaney; Omorogbe, Jacqueline; Tango, Dana; Tolomeo, Pam; et al.
Abstract : In a cohort of inpatients with hematologic malignancy and positive enzyme immunoassay (EIA) or polymerase chain reaction (PCR) Clostridium difficile tests, we found that clinical characteristics and outcomes were similar between these groups. The method of testing is unlikely to predict infection in this population, and PCR-positive results should be treated with concern. Infect Control Hosp Epidemiol 2018;863–866